The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14455/isec.res.2019.142
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Government Initiatives on Implementing Sustainable Infrastructure Construction

Abstract: Sectoral development activities, lack of standards on eco-systematic approach, prioritizing short-term outcomes, and ignoring the holistic and comprehensive prospects of sustainability have led to environmental degradation. Therefore, the Indonesian government has realized the importance of implementing sustainable development concepts in every phase of infrastructure project life-cycle. This paper reviews the existing government regulations on sustainable construction implementation guidelines, which underlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other driving factors in the application of sustainable construction is the existence of environmental support for the development of the construction market, the economic value of green construction, the level of social participation of elements of society, as well as the ecological value [22]. The concept of sustainable construction is still considered a model of development that is high cost and exclusive in value so that there is still a perception that thinks that only certain buildings or certain locations can implement sustainable principles, so that in this condition the role of government is needed in developing strategies to lead the sustainability agenda by evaluating various Project proposals in meeting the sustainability criteria, in the project planning phase, must be based on procurement and the green construction process, then for the construction implementation must be built by trained and competent contractors taking into account the technical aspects of sustainability [4] In the implementation of sustainable construction in the development of the Likupang Special Economic Zone, it certainly becomes an important note regarding the level of involvement and concern of the government in leading and motivating all elements or parties interested in the development of the Likupang SEZ, to support government programs in promoting tourism and the economy of the North Sulawesi region. Local government concern in achieving successful implementation of sustainable construction must consistently implement sustainable principles-based construction starting from the procurement stage, by establishing criteria in the selection of service providers that emphasize green construction throughout the product life cycle procurement process [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other driving factors in the application of sustainable construction is the existence of environmental support for the development of the construction market, the economic value of green construction, the level of social participation of elements of society, as well as the ecological value [22]. The concept of sustainable construction is still considered a model of development that is high cost and exclusive in value so that there is still a perception that thinks that only certain buildings or certain locations can implement sustainable principles, so that in this condition the role of government is needed in developing strategies to lead the sustainability agenda by evaluating various Project proposals in meeting the sustainability criteria, in the project planning phase, must be based on procurement and the green construction process, then for the construction implementation must be built by trained and competent contractors taking into account the technical aspects of sustainability [4] In the implementation of sustainable construction in the development of the Likupang Special Economic Zone, it certainly becomes an important note regarding the level of involvement and concern of the government in leading and motivating all elements or parties interested in the development of the Likupang SEZ, to support government programs in promoting tourism and the economy of the North Sulawesi region. Local government concern in achieving successful implementation of sustainable construction must consistently implement sustainable principles-based construction starting from the procurement stage, by establishing criteria in the selection of service providers that emphasize green construction throughout the product life cycle procurement process [6].…”
Section: Resultsmentioning
confidence: 99%
“…The programming stage, the government must have a strategy to lead the sustainability agenda including providing indicators that can be used to evaluate proposed projects that meet sustainability criteria [4]. The next phase is project planning, which must be based on procurement and the green construction process.…”
Section: Introductionmentioning
confidence: 99%
“…It needs full support from the government as a regulatory regulator to socialize sustainable construction to all stakeholder components so that a common understanding between the government and service providers, investors and the community, about sustainable construction is very important to support the implementation of sustainable construction principles (Willar and Pangemanan, 2019). In addition, Lingga and Pratomo in a study of the SEZ area of Sei Mangkei, showed that the development of SEZ must be in harmony with the development of social life and improving the economy of the surrounding community.…”
Section: Introductionmentioning
confidence: 99%